Effect of enzyme‐assisted hydrolysis on protein pattern, technofunctional, and sensory properties of lupin protein isolates using enzyme combinations. Issue 7 (1st December 2019) - Schlegel, Katharina; Sontheimer, Katharina; Eisner, Peter; Schweiggert‐Weisz, Ute
Abstract: The modification of lupin protein isolates (LPI) by means of enzymatic hydrolysis ( Lupinus angustifolius cultivar Boregine) was performed with four enzyme preparations (Alcalase 2.4 L, Papain, Corolase 7089, and Neutrase 0.8 L) in a one‐ and two‐step process to determine the efficacy for the destruction of major IgE‐reactive polypeptides and the evaluation of the technofunctional and sensory properties of lupin protein hydrolysates. Combinations of Alcalase 2.4 L and Papain were most effective in the degradation of polypeptides in L. angustifolius as measured by sodium dodecylsulfate–polyacrylamide gel electrophoresis. The enzymatic hydrolysis of the LPI increased their technofunctional properties such as protein solubility, foam activity, and emulsifying capacity almost independently of the enzyme preparation used. The sensory results showed a significant increase in bitterness from 1.9 for LPI to 5.7 for the combination of Alcalase 2.4 L and Papain in one‐step process. The aroma attributes of the hydrolysates were very similar to untreated LPI. The results of this study show the possibility of enzymatic hydrolysis of LPI to destroy the major IgE‐reactive polypeptides that increase the technofunctional properties of the isolates and thus their use in human nutrition as food ingredients. Abstract : Modification of lupin protein isolate (LPI) by enzymatic hydrolysis of LPIs ( Lupinus angustifolius cultivar Boregine) was carried out with four enzyme preparations in a one‐step and two‐step process to determine the efficacy for the destruction of important IgE‐reactive polypeptides and the evaluation of the technofunctional and sensory characteristics of lupin hydrolysates. Combinations of Alcalase 2.4 L and Papain were most efficient in the destruction of polypeptides in L. angustifolius measured by sodium dodecylsulfate–polyacrylamide gel electrophoresis. Most of the proteolytic enzymes increased the technofunctional properties such as protein solubility, foam activity, and emulsifying capacity of untreated LPI. The aroma attributes of the hydrolysates were very similar to the LPI. The results of this study show the possibility of enzymatic hydrolysis of LPI to destroy the main IgE‐reactive polypeptides that increase the technofunctional properties of the isolates and therefore their use for human nutrition as food ingredient.